Geographic distribution and conservation status of Eulychnia ritteri Cullmann (Cactaceae), an endemic cactus from southern Peru - Pauca-Tanco, Gregory Anthony (2021)
Eulychnia ritteri is endemic to Peru, restricted to the northern coast of the department of Arequipa. The lack of knowledge of this species, and threats such as human activities and climate change, put the populations at risk. In this research, we examined the geographical distribution and conservation status of E. ritteri in the coastal area of the Caravelí province. In addition, the population structure and phenology in the Quebrada Vizcachani population were evaluated using plots of 10x100 m. Data on the accompanying flora and local fauna were also obtained. Eulychnia ritteri showed five populations distributed from 15°43’ to 15°47’S, with a total area of 63.62 ha (0.63 km2). The Quebrada Vizcachani population is the largest (24.5 ha) and the Cementerio population the smallest (0.018 ha). The population density evaluated is 0.06 ind/m2, where seedlings, juveniles, adults, and dead plants were 3.61, 24.09, 56.63 and 15.67% respectively. The phenology was asynchronous, the flower buds, flowers and fruits appear in the same period. The flowers and fruits were food for insects and rodents respectively, and 18 accompanying species have been recorded. Finally, E. ritteri is categorised as endangered (EN), given its geographical distribution and identified threats.